High-impact jumping mitigates the short-term effects of low energy availability on bone resorption but not formation in regularly menstruating females: A randomized control trial - Hutson, M. J.; O'Donnell, E.; Brooke-Wavell, K.; James, L. J.; Raleigh, C. J.; Carson, B. P.; Sale, C.; Blagrove, R. C. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Low energy availability (LEA) is prevalent in active individuals and negatively impacts bone turnover in young females. High-impact exercise can promote bone health in an energy efficient manner and may benefit bone during periods of LEA. Nineteen regularly menstruating females (aged 18-31 years) participated in two three-day conditions providing 15 (LEA) and 45 kcals kg fat-free mass-1 day-1 (BAL) of energy availability, each beginning 3 ± 1 days following the self-reported onset of menses. Participants either did (LEA+J, n = 10) or did not (LEA, n = 9) perform 20 high-impact jumps twice per day during LEA, with P1NP, ß-CTx (circulating biomarkers of bone formation and resorption, respectively) and other markers of LEA measured pre and post in a resting and fasted state. Data are presented as estimated marginal mean ± 95% CI. P1NP was significantly reduced in LEA (71.8 ± 6.1-60.4 ± 6.2 ng mL-1, p < 0.001, d = 2.36) and LEA+J (93.9 ± 13.4-85.2 ± 12.3 ng mL-1, p < 0.001, d = 1.66), and these effects were not significantly different (time by condition interaction: p = 0.269). ß-CTx was significantly increased in LEA (0.39 ± 0.09-0.46 ± 0.10 ng mL-1, p = 0.002, d = 1.11) but not in LEA+J (0.65 ± 0.08-0.65 ± 0.08 ng mL-1, p > 0.999, d = 0.19), and these effects were significantly different (time by condition interaction: p = 0.007). Morning basal bone formation rate is reduced following 3 days LEA, induced via dietary restriction, with or without high-impact jumping in regularly menstruating young females. However, high-impact jumping can prevent an increase in morning basal bone resorption rate and may benefit long-term bone health in individuals repeatedly exposed to such bouts.